Analisis Bibliometrik Penelitian Mujawwad Al-Quran pada Database Dimentions - Amira Meina Zahro; Busro Busro (Gunung Djati Conference Series, 2023)
This study seeks or aims to find out the aesthetics of reading the Koran with recitations of the mujawwad style of the Koran, and to beautify the recitation of the Koran. This study uses the bibliometric method on database dimensions so that data can be found to be analyzed in the categories of research, development of publications, productive researchers, and places of publication related to the mujawwad Al-Qur'an research. To get the data, five stages were carried out including determining keywords, then searching data, selecting articles, validating data and also analyzing data. The results obtained from this study found the highest research category, namely mujawwad al-quran, which of course this research continues to grow every year so that the highest research is found in 2021, with the most productive researcher, namely Cut Fauziah, and the place of publication that publishes the most, namely the journal at -tibyan. It can be illustrated how important aesthetics is in reciting the holy verses of the Koran through this mujawwad method. Thus the mujawwad study of the Koran needs to be developed and maintained more.